Current issues in European financial and insolvency law : perspectives from France and the UK - Ringe, Wolf-Georg, 1976-; Gullifer, Louise; Théry, Philippe (Studies of the Oxford Institute of European and Comparative Law, 2009)
Recent case-law and legislation in European company and insolvency law have significantly furthered the integration of European business regulation. In particular, the case-law of the European Court of Justice and the introduction of the EU Insolvency Regulation have provided the stimulus for current reforms in various jurisdictions in the fields of insolvency and financial law. The UK, for instance, has adopted the Enterprise Act in 2002, designed, inter alia, to enhance enterprise and to strengthen the UK's approach to bankruptcy and corporate rescue. In a similar vein, a recent reform in Fr.